METHODS OF SEARCHING ELECTRONIC EDUCATIONAL RESOURCES RELATED TO SCIENCE ON THE INTERNET - Adas Sultanova (Web of Journals Publishing, 2024)
Professional development requires a great responsibility to work with students on a logical basis of integrated pedagogical processes, to provide them with educational innovations and to achieve development.
Keywords: Internet network, scientific electronic resources, search systems, web browsers, computers, web page, information search.